2006
DOI: 10.1007/s00216-006-0470-x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal diffusion behavior of hemicyanine dyes across phospholipid vesicle membranes as studied by second-harmonic generation and fluorescence spectroscopies

Abstract: The adsorption and longitudinal diffusion behaviors of a series of hemicyanine dyes to phospholipid vesicle membranes were studied by second-harmonic generation (SHG) and fluorescence spectroscopies. It was observed that the longitudinal diffusion of cationic hemicyanine dyes takes place immediately after the initial adsorption of these dyes to the outer surface of the vesicle membrane. In contrast, hardly any amount of a zwitterionic hemicyanine dye with a sulfonate group diffused across the vesicle membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 24 publications
6
29
1
Order By: Relevance
“…All these advantages of SHG have already been used to probe the diffusion of an aromatic compound across a biological membrane 8. 9 In this very specific application, it is in fact the decrease of the second harmonic signal that is followed, since in this case diffusion gives rise to oppositely oriented molecules at the inner part of the bilayer in comparison with molecules only being present at the outer surface.…”
Section: Introductionmentioning
confidence: 99%
“…All these advantages of SHG have already been used to probe the diffusion of an aromatic compound across a biological membrane 8. 9 In this very specific application, it is in fact the decrease of the second harmonic signal that is followed, since in this case diffusion gives rise to oppositely oriented molecules at the inner part of the bilayer in comparison with molecules only being present at the outer surface.…”
Section: Introductionmentioning
confidence: 99%
“…It was expected that the rate of transport across the CM should be similar to those obtained from prior liposome‐based studies . In both cases, the molecular probe has to directly diffuse across the lipid bilayer.…”
Section: Molecule—membrane Interactions Monitored With Second Harmonimentioning
confidence: 99%
“…Following this demonstration,anumber of studies have since examined the effects of lipid composition and av ariety of environmental factorso nt he propensity and characteristics of molecular transport across membranes in model liposome systems. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] The studies on liposomes suggested the feasibility that SHS could be used for monitoring molecular transport across membranesi nl iving biological cells. Indeed, in 2010, our laboratory reportedt he first demonstration that SHS could be applied to study molecular transport across membranes in living cells.…”
Section: Introductionmentioning
confidence: 99%
“…[7] All these advantages of SHG have already been used to probe the diffusion of an aromatic compound across a biological membrane. [8,9] In this very specific application, it is in fact the decrease of the second harmonic signal that is followed, since in this case diffusion gives rise to oppositely oriented molecules at the inner part of the bilayer in comparison with molecules only being present at the outer surface.…”
Section: Introductionmentioning
confidence: 97%